Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.5 - Integrated Review - Radicals and Rational Exponents - Page 720: 7



Work Step by Step

$\sqrt[5] {-32y^{5}}$ =$\sqrt[5] {-32\times y^{5}}$ =$\sqrt[5] {-32} \times \sqrt[5] {y^{5}}$ =$\sqrt[5] {(-2)^{5}} \times \sqrt[5] {y^{5}}$ =$-2\times y$ =$-2y$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.